Association between oral corticosteroid starting dose and the incidence of pneumonia in Japanese patients with ulcerative colitis: a nation-wide claims database study - Katsuyoshi Matsuoka; Tomoyuki Inoue; Hiroaki Tsuchiya; Katsumasa Nagano; Toshiyuki Iwahori (Intestinal Research, 2024)
Background/Aims A previous study demonstrated that half of patients started oral corticosteroids (OCS) for ulcerative colitis (UC) exacerbations at lower doses than recommended by Japanese treatment guidelines (initial OCS prednisolone equivalent dose, 30–40 mg). This may relate to physician’s concern about infection, especially pneumonia including Pneumocystis jirovecii pneumonia (PJP), from high OCS doses. We assessed whether pneumonia incidence is increased with guideline-recommended OCS initial doses. Methods This retrospective cohort study used the Japan Medical Data Center claims database (2012–2021). The whole cohort consisted of all UC patients who started OCS during the study period meeting the inclusion and exclusion criteria. The matched cohort was created by propensity score matching; the lower (initial OCS dose < 30 mg), guideline-recommended (30–40 mg), and higher groups ( > 40 mg) in a 2:2:1 ratio. Pneumonia incidence in the primary analysis was evaluated in the matched cohort. A Poisson regression model determined pneumonia-related risk factors in the whole cohort. Results After screening, 3,349 patients comprised the whole cohort; 1,775 patients comprised the matched cohort (lower dose, n = 710; guideline-recommended dose, n = 710; higher dose, n = 355). The incidence of any pneumonia was low; no differences were observed in incidence rates across these dose subgroups. In total, 3 PJP cases were found in the whole cohort, but not detected in the matched cohort. Several risk factors for any pneumonia were identified, including age, higher comorbidities index, treatment in large facility and hospitalization. Conclusions The incidence of pneumonia, including PJP, in UC patients was low across initial OCS dose treatment subgroups.